Breast conserving therapy is associated with improved overall survival compared to mastectomy in early-stage, lymph node-negative breast cancer. (January 2020) - Almahariq, Muayad F.; Quinn, Thomas J.; Siddiqui, Zaid; Jawad, Maha S.; Chen, Peter Y.; Gustafson, Gregory S.; Dilworth, Joshua T.
Highlights: Breast conserving therapy (BCT) is associated with higher OS compared to mastectomy. The benefit of BCT is highest in women with a high Recurrence Score and >50 years. These findings warrant prospective validation. Abstract: Background and purpose: Recent retrospective studies suggest improved overall survival (OS) with breast conserving therapy (BCT), including breast conserving surgery and adjuvant whole breast radiotherapy, compared to mastectomy in the modern era. The patient subset most likely to benefit from BCT remains unclear, and the role of Oncotype DX Recurrence Score (RS) in this context is unknown. We compared BCT to mastectomy in early-stage, node-negative breast cancer. We further explored outcomes after stratification by RS and age. Materials and methods: We performed a matched-cohort analysis of National Cancer Database (NCDB) patients with pT1-2, pN0, cM0 breast cancer treated between 2006 and 2014 with BCT or mastectomy. Patients were matched for all available baseline characteristics using propensity scores with inverse probability of treatment weighting (IPTW) with stabilized weights. Results: We identified 144, 263 eligible patients treated with BCT and 87, 379 patients treated with mastectomy. After IPTW-matching, OS was higher with BCT compared to mastectomy: 5-year OS of 94.4% vs. 91.8% ( P < 0.001) and 7-year OS of 90% vs. 85.2% ( P < 0.001). Doubly robust multivariable analysis showed an association between BCT and improved OS (HR 0.66, 95% CI, 0.64–0.69, P < 0.001). In a subset analysis, BCT was associated with improved OS in patients with RS >25, but not patients with RS ≤25. When stratified by age, only patients >50 years had improved OS with BCT. Conclusion: BCT is associated with improved OS compared to mastectomy in women with early-stage, node-negative breast cancer. The improvement in OS with BCT appears to be most pronounced in patients with high RS and >50 years of age. Prospective validation of these findings is required.